2020
DOI: 10.1111/adb.12965
|View full text |Cite
|
Sign up to set email alerts
|

Low‐dose alcohol: Interoceptive and molecular effects and the role of dentate gyrus in rats

Abstract: Alcohol abuse and dependence are world‐wide health problems. Most research on alcohol use focuses on the consequences of moderate to high levels of alcohol. However, even at low concentrations, alcohol is capable of producing effects in the brain that can ultimately affect behavior. The current studies seek to understand the effects of low‐dose alcohol (blood alcohol levels of ≤10mM). To do so, these experiments utilize a combination of behavioral and molecular techniques to (1) assess the ability of the inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 63 publications
0
6
1
Order By: Relevance
“…As we were interested in necessity, we aimed for asymptotic inactivations with a 2mM muscimol dose. This is still considered moderate with respect to the broader literature, with 'high' being in the 5-8mM range (Katz et al, 2016;Randall et al, 2021). However, our pilot data suggest that higher doses do not increase effect sizes.…”
Section: Discussioncontrasting
confidence: 50%
“…As we were interested in necessity, we aimed for asymptotic inactivations with a 2mM muscimol dose. This is still considered moderate with respect to the broader literature, with 'high' being in the 5-8mM range (Katz et al, 2016;Randall et al, 2021). However, our pilot data suggest that higher doses do not increase effect sizes.…”
Section: Discussioncontrasting
confidence: 50%
“…Low‐dose ethanol may affect different reward‐related circuits in males and females, which could contribute to the differences in ethanol effects observed here. Some differences in the neural circuit effects of low‐dose ethanol have been observed (Bryant et al., 2023; Cui & Koob, 2017; Randall et al., 2020), but this has yet to be thoroughly investigated in both male and female animals and as a result of chronic, as opposed to acute, exposure. Identifying the neurobiological substrates impacted by chronic low‐dose ethanol exposure may uncover new therapeutic targets to assist in preventing the development of inflexible behaviors that is associated with transition from casual drinking to AUD.…”
Section: Discussionmentioning
confidence: 99%
“…Only a small percentage of people who casually drink alcohol (~10%) go on to be diagnosed with or to develop an alcohol use disorder (AUD) (SAMHSA, 2021), but there is increasing evidence that exposure to even low doses of ethanol can impact the brain and behavior (Bryant et al., 2023; Cui & Koob, 2017; Randall et al., 2020). While it is known that chronic high‐dose ethanol exposure can promote the development of inflexible behaviors such as habits (Dickinson et al., 2002; O'Tousa & Grahame, 2014; Vandaele & Ahmed, 2021) that are hallmarks of AUD (McKim et al., 2016; Sjoerds et al., 2013), the consequences of lower doses of ethanol are less well‐characterized.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple brain regions known to be important for the encoding and updating of reward value information are impacted by chronic ethanol ( Lescaudron and Verna, 1985 ; DePoy et al, 2013 ; Barker et al, 2015 ; Trantham-Davidson et al, 2017 ; Ewin et al, 2019 ), and may be targets for the low dose ethanol effects observed here. In particular, the infralimbic prefrontal cortex, nucleus accumbens shell, and dentate gyrus have been shown to be activated as a result of low dose ethanol using c-Fos and Arc as markers of neuronal activity in rats, and this was not impacted by sex ( Randall et al, 2020 ). Additionally, it has been shown that brain-derived neurotrophic factor (BDNF) is increased in the hippocampus following low to moderate alcohol consumption ( Tizabi et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%